Soil types influence the fate of antibiotic-resistant bacteria and antibiotic resistance genes following the land application of sludge composts. (September 2018) - Zhang, Junya; Sui, Qianwen; Tong, Juan; Zhong, Hui; Wang, Yawei; Chen, Meixue; Wei, Yuansong
Abstract: Sewage sludge was generally considered a significant reservoir of antibiotic resistance genes (ARGs) and could enter agricultural systems as fertilizer after composting. Soil types and the discrepancy of sludge composts could have influenced the fate of antibiotic-resistant bacteria (ARB) following the land application of sludge composts, which deserved to be clarified. Thus, the fate of ARB and ARGs following the land application of three types of sludge composts (A, B, and C) to three different soils (red soil, loess, and black soil) was investigated. The results showed that tetX, which was enriched the most during composting, did not affect the soil resistome, whereas tetG did. Soil types influenced the dynamics of ARB and ARGs significantly, whereas no significant difference was observed among compost types. The advantage of reducing ARGs during the composting process in compost B did not extend to land application. Land application of composts influenced the microbial community significantly at the early stage, but the microbial community returned to the control pattern gradually. Changes in the microbial community contributed more to the dynamics of ARGs in red and black soil compared with other factors, including co-selection from heavy metals, horizontal gene transfer, biomass and environmental factors, whereas horizontal gene transfer, reflected by intI1 levels, contributed the most in loess. Graphical abstract: Highlights: Soil types contribute more to the fate of antibiotic resistance than composts. Sludge composts led to ARB enrichment especially resistance to cefotaxime in soils. The tetG could be the biomarker for evaluating land application of sludge compost. The advantage of ARGs reduction in sludge composting did not extend to the soils. The main contributor to the evolution of ARGs varied from soil types.